Determinants of treatment disengagement among those at risk of suicide referred to primary mental health care services in Western Sydney, Australia. (March 2021) - Munasinghe, Sithum; Page, Andrew; Mannan, Haider; Ferdousi, Shahana; Peek, Brendan
Objective: Continued engagement with primary mental health services has been associated with the prevention of subsequent suicidal behaviour; however, there are few studies that identify determinants of treatment disengagement among those at risk of suicide in primary care settings. This study investigated determinants of treatment disengagement of those at risk of suicide who were referred to primary mental health care services in Western Sydney, Australia. Method: This study used routinely collected data of those referred for suicide prevention services provided through primary mental health care services between July 2012 and June 2018. Associations between sociodemographic, diagnostic, referral- and service-level factors and treatment non-attendance and early treatment cessation were investigated using a series of multivariable generalised estimation equations. Results: There were 1654 suicidal referrals for 1444 people during the study period. Those identified with a risk of suicide were less likely to never attend treatments (16.14% vs 19.77%), but were more likely to disengage earlier from subsequent service sessions (16.02% vs 12.41%), compared to those with no risk of suicide. A higher likelihood of non-attendance to any primary mental health care service sessions was associated with those aged 25–44, lower socioeconomic status, a presentation for substance use and a referral from acute care (either emergency department or hospital). Among those who attended an initial treatment session, younger age (18–24 years) and a longer waiting time for an initial follow-up appointment were associated with a higher likelihood of early treatment cessation from primary mental health care services. Conclusion: These findings can inform potential strategies in routine primary mental health care practice to improve treatment engagement among those at risk of suicidal behaviour. Youth-specific interventions, behavioural engagement strategies and prompt access to services are policy and service priorities.